Audiovisual industry and the structural factors of the television crisis - Richeri, Giuseppe (MATRIZes, 2017)
This article analyzes the current state of traditional television financing resources, detecting a critical situation in its three main sources (advertising, signatures and service charges). Next, it discusses the most dynamic part of the television sector: Video on Demand (VoD) and Subscription Video on Demand (SVoD) services, which could generate new resources for audiovisual production. However, the analysis of the catalogs of these services shows a low supply of European films compared to the United States. Thus, as on other occasions, the development of new television services and new business models could be a missed opportunity for the European audiovisual industry.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE2MDYvaXNzbi4xOTgyLTgxNjAudjExaTFwMTMtMjQ